Application of Transcriptome Analysis to Understand the Adverse Effects of Hypotonic Stress on Different Development Stages in the Giant Freshwater Prawn Macrobrachium rosenbergii Post-Larvae - Bo Liu; Qiang Gao; Bo Liu; Changyou Song; Cunxin Sun; Mingyang Liu; Xin Liu; Yunke Liu; Zhengzhong Li; Qunlan Zhou; Hao Zhu (MDPI AG, 2022)
Salinity is one of the important environmental factors affecting survival and growth of aquatic animals. However, the impact of low-salinity stress on M. rosenbergii post-larvae at different development stages remains elusive. Therefore, the aim of this study was to explore the underlying mechanisms of hypotonic stress at different development stages of M. rosenbergii post-larvae through transcriptome analysis and antioxidant parameters detection. The salinity of the control group was 15 psu (S15) and the hypotonic stress group was 6 psu (S6). Samples were collected at 7 days-post-hatch (dph), 14 dph and 21 dph larvae. The results showed that hypotonic stress caused oxidative damage in post-larvae evidenced by decreased glutathione peroxidase (GSH-Px); superoxide dismutase (SOD); anti-superoxide anion free radical (ASAFR); and increased malondialdehyde (MDA); nitric oxide (NO); and inducible nitric oxide synthase (iNOS) levels. Transcriptome analysis showed that there were 1428, 1187, 132 DEGs including 301, 366, 4 up-regulated genes and 1127, 821, 128 down-regulated genes at 7 dph, 14 dph and 21 dph larvae under hypotonic stress, respectively. Furthermore, GO and KEGG enrichment indicated that hypotonic stress led to dysregulation of immune signals including lysosome and autophagy in the 7 dph larvae. The autophagy-related genes including beclin 1-associated autophagy-related key regulator (Barkor); ubiquitin-like modifier-activating enzyme ATG7 (ATG7); Beclin; autophagy-related protein 13 (ATG13); nuclear receptor-binding factor 2 (Nrbf2); ubiquitin-like-conjugating enzyme ATG3 (ATG3); vacuole membrane protein 1 (VMP1); and autophagy-related protein 2 (ATG2) decreased at 7 dph, and 14 dph larvae, and then increased at 21 dph larvae under hypotonic stress. In the 14 dph and 21 dph larvae, the renin-angiotensin system was activated. In conclusion, our data indicated that hypotonic stress reduced the antioxidant capacity and impaired the immune system in post-larvae, but as development progresses, the adaptability of post-larvae to hypotonic stress gradually increased, and might reach a new homeostasis through the RAS signaling pathway.